ילידיות ואלימות בשירת שנות החמישים והשישים - חבר חנן (מכאן, 2024)
The article examines the relationship between nativist representations in Hebrew poetry of the young state of Israel in the 1950s and 1960s, and the justification of Israel’s violent struggle for sovereignty during the 1948 war and the Palestinian Nakba. The article focuses on the ways in which the composition and figurative language of the poems either confirmed or negated the national narrative, which justified the violence of sovereignty by means of the natural organicism of Jewish nativism. The national narrative built by the poetry of the 1950s and 1960s was examined using the hermeneutic model developed by Menachem Perry and Yosef Haefrati in an article published in 1966 in Achshav (Now), the main stage on which the self-consciousness of the poetry of the period was formed. This literary consciousness is referred to in contemporary literary discourse as the “literature of the state generation,” that is, the literary sensibility emerging in the context of the nascent state’s achievement of sovereignty. In their groundbreaking article, Perry and Haefrati offered a new reading of the poetry of the national poet Haim Nachman Bialik. They presented their reading as an alternative to the longstanding tradition whereby Bialik’s poetry was read on the assumption that the poem’s narrative was both progressive and continuous. Their reading of Bialik’s poem “I Did Not Gain the Light of No Man’s Land” suggests it is a reversible poem breaking the continuity of the transition from the originary poetic “spark” to its ownership. An allegorical reading of this disruption shows the national poet’s sovereign narrative to be fragmented, thus making it impossible to justify sovereign violence by referring back to the originality and organicism of the native. This compositional reversal also enables to show how prominent poets of this period, such as Nathan Zach, Dahlia Ravikovitch and Yehuda Amichai, challenged the justification of violence that bases itself in the authority of the native. The article devotes special attention to the ways in which the poets of the 1950s and 1960s attacked nativist poetic representations of the War of Independence and the catastrophe of the Palestinian Nakba. The article shows how national allegory, a concept underpinning Perry and Haefrati’s article, expresses fracture, destruction, and heterogeneity. This national allegory makes it possible to define the sovereignty of the fledgling state as a heterogeneous and “post- Westphalian” sovereignty, rather than a stable, continuous, and homogeneous sovereignty enfolding an uninterrupted transition between the organic Jewish native and violence.